The impact of Kuroshio water on the source water of the southeastern Taiwan Strait： numerical results - Zhang, Wenzhou; Zhuang, Xuefen; Chen, Chentung Arthur; Huang, Tinghsuan (Acta oceanologica Sinica, 2015)
Model output from a Pacific basin-wide three-dimensional physical-biogeochemical model during the period of 1991 to 2008 was used to investigate the impact of Kuroshio water on the source water of the southeastern Taiwan Strait. Based on the characteristic salinities of both Kuroshio water and the South China Sea water, a Kuroshio impact index （KII） was designed to measure the degree of impact. The KII correlates significantly with the northeast-southwest component of wind stress, but the former lags the latter by approximately two months. The correlation coefficient between them increases from 0.267 4 to 0.852 9, with a lag time increasing from 0 to 63 days. The impact of Kuroshio Water is greater in winter and spring than in summer and autumn. At the interannual time scale, E1 Nifio and La Nifia events play an important role in impacting the KII. During E1 Nifio events, more Kuroshio water contributes to the source water of the southeastern Taiwan Strait. Conversely, during La Nifia events, less Kuroshio water contributes to the source water.